Delineating the Association of Component Traits and their Effects on Yield in Elite Rice (Oryza sativa L.) Genotypes of Telangana and Andhra Pradesh - Harisha, R.; Bhadru, D.; Vanisri, S.; shankar, V. Gouri; Bhargava, K.; Balakrishnan, Adithya P.; Rathan, N. D. (International Journal of Economic Plants, 2022)
The current study was conducted at Seed Research and Technology Center (SRTC), Professor Jayashankar Telangana State Agricultural University, Hyderabad, Telangana state, India to understand traits association with yield components and their direct and indirect influence on seed/grain yield during the kharif season (July to November) 2018–19. Eighteen elite rice genotypes were evaluated for eight yield attributing traits in randomized complete block design (RCBD) with three replications. Correlation study among the genotypes reveals that, genotypic correlation coefficients were slightly higher than phenotypic correlation coefficients for most traits showed the influence of genetic composition on the lines’ expression. Highly significant and positive strong correlation observed for days to maturity and days to 50% flowering (0.8955 and 0.8230), while moderate positive correlation observed for productive tillers plant-1 and panicle length (0.5744 and 0.3571) at genotypic and phenotypic level respectively. However, Seed yield plant-1 depicted a strong and positive correlation with thousand seed weight (0.4048 and 0.3895), while very low with number of productive tillers plant-1 (0.0579 and 0.0524) at the phenotypic and genotypic levels. The results of path analysis revealed that the thousand seed weight has a high and significant genotypic (0.3286*) and phenotypic path coefficient value (0.3198) indicates high positive direct effects on the seed yield and days to 50% flowering (0.2252) shows strong and positive direct impact on the seed yield. These traits could be used as selection criteria to improve the grain yield and grain quality in the rice breeding programs.